Effects of PMA (PHORBOL-12-MYRISTATE-13-ACETATE) on the Developing Rodent Brain. (30th March 2015) - Dzietko, Mark; Hahnemann, Maria; Polley, Oliver; Sifringer, Marco; Felderhoff-Mueser, Ursula; Bührer, Christoph
Abstract : Perinatal infections have a negative impact on brain development. However, the underlying mechanisms leading to neurological impairment are not completely understood and reliable models of inflammation are urgently needed. Using phorbol-myristate-acetate as an activator of inflammation, we investigated the effect on the developing rodent brain. Neonatal rats and mice deficient in IL-18 or IRAK-4 were exposed to PMA. Brains were assessed for regulation of pro- and anti-inflammatory cytokines and cell death 24 hrs, 7 and 14 days after treatment. PMA induced an inflammatory response and caused widespread neurodegeneration in the brains of 3- and 7-day-old rats. In contrast, 14-day-old rats were resistant to the neurotoxic effect of PMA. Histological evaluation at the age of 14 and 21 days revealed a destruction of the cortical microstructure with decreased numerical density of neuronal cells. Mice deficient in IL-18 or IRAK-4 were protected against PMA induced brain injury. PMA treatment during a vulnerable period can alter brain development. IL-18 and IRAK-4 appear to be important for the development of PMA induced injury.